Water pollution control in emerging and transitional countries (International Journal of Food and Nutritional Sciences, 2022)
The policy prescription for resolving environmental issues in developing and transitional countries (CIT) is gradually polarizing into two camps. Market-based instruments (MBIs) are widely used in these nations, according to one set of academics and policy supporters, including international organizations. The opposing viewpoint is that institutions must be created first, or that policymakers should choose a gradual or tiered strategy that takes into consideration current capabilities. Environmental control in these nations, according to the organization, is more difficult than in developed countries due to financial, institutional, and political limitations. In the near term, the urgent requirements of developing nations may be successfully handled by learning from the challenges faced by a few successful instances and creating an appropriate policy instrument in response. In this article, three such examples from three distinct regions of the world—Malaysia (Asia-Pacific), Poland (Eastern Europe), and Colombia—have been highlighted (Latin America). The study investigates whether policy tools resulted in lower levels of water pollution in these nations, as well as what role MBIs had in pollution reduction. According to the case studies, an overall improvement in environmental compliance was achieved via a mix of instruments—license fees, standards, charges, and subsidies—enforced by aggressive enforcement